Open source forensic tools for linux hard disk investigation [electronic resource] - Bashar (Moh'd Walid) Amin Maree, 1970- (2010)
Thesis (Sarjana Sains (Sains Komputer - Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2010